PENGARUH FAKTOR BUDAYA DAN DIGITAL MARKETING TERHAHAP KEPUTUSAN PEMBELIAN WAYANG KULIT DI KAMPUNG WAYANG DESA KEPUHSARI MANYARAN WONOGIRI - Putri, Estinigtyas Anggiri; Widiastuti, Erni (Universitas Of Surakarta, 2024)
The purpose of this study was to determine the influence of cultural factors and digital marketing on purchasing decisions for shadow puppets in Wayang Village, Kepuhsari Manyaran Wonogiri. This research is a quantitative research. The sampling technique used is purposive sampling, with a sample of 100 respondents from consumers or people who have bought leather puppets in Wayang Village. Primary data obtained from questionnaires that have been distributed via google form. The analysis technique used is validity test, reliability test, descriptive analysis, multiple linear regression, F test, t test, and determination test (R2). Based on the F test and t test, the results obtained were that the variable cultural factors and digital marketing partially or simultaneously had a positive and significant effect on the purchasing decision of shadow puppet in Wayang Village. In this study, the coefficient of determination (R2) was obtained at 0.430. This shows that 43% of the decision to purchase shadow puppets in Wayang Village is influenced by variations in the two independent variables, namely cultural factors and digital marketing. While the remaining 57% is influenced by other variables not examined in this study.